2014
DOI: 10.1016/j.aju.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

An early-detection programme for prostate cancer in Saudi men: A call from a tertiary-care centre in the Eastern province

Abstract: ObjectiveTo review the mode of presentation and clinical course of patients with prostate cancer during a specified period, as the detection rate is tending to increase, with most patients presenting at an advanced stage, and yet the overall incidence and prevalence rates are low.Patients and methodsWe retrospectively reviewed all aspects of care for patients who were diagnosed between May 2006 and July 2010.ResultsIn all, 76 men had a histologically confirmed prostatic adenocarcinoma diagnosed between May 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Of the 54 patients who had staging imaging, 27 (50%) had lymph node metastasis, 12 (22%) had pulmonary metastasis, and 6 (11%) had liver metastasis. 15 This is contrary to the lower rate of extraprostatic disease in the US. According to the SEER database, out of a sample size of 2,795,592 men, 2,264,430 (81%) prostate cancer patients present with localized disease, 335,471 (12%) with regional lymph node metastasis, and only 111,824 (4%) with distant metastasis.…”
Section: Evidence Acquisitionmentioning
confidence: 71%
“…Of the 54 patients who had staging imaging, 27 (50%) had lymph node metastasis, 12 (22%) had pulmonary metastasis, and 6 (11%) had liver metastasis. 15 This is contrary to the lower rate of extraprostatic disease in the US. According to the SEER database, out of a sample size of 2,795,592 men, 2,264,430 (81%) prostate cancer patients present with localized disease, 335,471 (12%) with regional lymph node metastasis, and only 111,824 (4%) with distant metastasis.…”
Section: Evidence Acquisitionmentioning
confidence: 71%
“…First, the lack of practice using the formal prostate-specific antigen (PSA) test as a screening or early detection tool in Saudi Arabia could contribute to this increase. 7 Despite that fact that some studies have questioned the sensitivity of the PSA test in detecting PCa, many studies showed that introducing PSA screening into clinical practice contributed to reducing the incidence of PCa cases, especially those in the late and advanced stages. [8][9][10] Moreover, the rapid growth in the socioeconomic status and macroeconomics of Saudi Arabia could be another possible cause for the increase in the incidence of PCa over the study, as different studies have linked the incidence of PCa and economic status.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to either very low utilization of the device due to patient low acceptance or limited recommendation of these devices by the surgeons, or it could be attributed to the limited number of radical prostatectomies performed in Saudi Arabia. [ 15 ] Most of these devices were performed in government hospitals, which might be the same hospitals that perform the radical prostatectomies.…”
Section: Discussionmentioning
confidence: 99%